Water chemistry, landscape, and spatial controls of δ13C and δ15N of zooplankton taxa in boreal lakes: One size does not fit all. (27th August 2019) - Anas, M. U. Mohamed; Scott, Kenneth A.; Wissel, Björn
Abstract: Carbon (δ 13 C) and nitrogen (δ 15 N) stable isotope ratios of zooplankton are potentially good indicators of energy and nutrient fluxes, and trophic interactions in lake food‐webs, yet, are poorly understood. Based on a synoptic survey of 233 boreal lakes, we evaluated the relationships of water chemistry, hydromorphological, and land cover variables (lake/catchment‐specific factors), and the spatial position of lakes in the landscape (representing potential regional factors) with the δ 13 C and δ 15 N of nine meso‐zooplankton taxa. The δ 13 C variation of most taxa was negatively related to water chemistry variables associated with allochthonous inputs (colour/dissolved organic carbon), and positively correlated with nutrient concentrations (together explaining 12–69% of variation). Most of the δ 13 C variation explained by significant hydromorphological and land cover variables (% peat area, drainage basin area:lake area, shoreline development index, and lake area, explaining 26–47% of variation) was shared by significant water chemistry variables. Together, this suggests that δ 13 C variation of zooplankton reflects different environmental influences on δ 13 C of lake primary producers. The δ 15 N variation of most taxa was significantly related to pH, total phosphorous concentration (water chemistry variables, explaining 8–64% of variation), and water retention time (hydromorphological variable, explaining 13–87% of variation). These relationships are probably reflective of the association of zooplankton δ 15 N with terrestrial organic matter flux, environmentally‐induced biogeochemical nitrogen transformations and phytoplankton 15 N fractionation. Specific water chemistry, hydromorphological, and land cover predictors of δ 13 C and δ 15 N and the direction of their effects (i.e. positive or negative) were largely similar among taxa. However, their degree of importance varied among taxa particularly for δ 13 C, probably due to contrasting feeding selectivity and resulting differences in allochthony. This suggests that δ 13 C of different taxa may respond differently to changes in limnological gradients due to environmental perturbations affecting boreal regions. The lake/catchment‐specific factors were more important than regional factors (lithology, soil properties and atmospheric nitrogen deposition; which are represented by the spatial position of lakes) in explaining δ 13 C and δ 15 N variation of zooplankton. Hence, before inferring regional effects in stable isotope studies, the influence of lake/catchment‐specific factors needs to be explicitly quantified.